Influence of the Form of a Solid Inclusionin an Inhomogeneous Liquid Droplet on the Conditionsof Its “Explosive” Destruction under Intense Heat Exchange - Nakoryakov V. E. Vladimir Eliferjevich (Mechanics, 2015)
Title screen